Presentation: The Party in the Andes - Hugues A., Juan (1974)
With this volume of Allpanchis we give our readers some documents that will help them approach a reality as complex as "La Fiesta en los Andes". We would have liked to reach an understanding of the festival, its forms and its contents, but we can only propose a first step, something like an introduction to some aspects, leaving the authors of the various articles responsible for their interpretations.